Self-Expandable Nitinol Stents for the Treatment of Nonmalignant Deep Venous Obstruction. (December 2020) - Sebastian, Tim; Gnanapiragasam, Suvetha; Spirk, David; Engelberger, Rolf Peter; Moeri, Laura; Lodigiani, Corrado; Kreuzpointner, Robert; Barco, Stefano; Kucher, Nils
Abstract : Background: Angioplasty with stent placement is a therapeutic option for patients with acute thrombotic, postthrombotic, and nonthrombotic obstruction of the iliofemoral veins or inferior vena cava. Previous studies of steel-alloy stents described variable patency rate across indications. Methods: The prospective Swiss Venous Stent Registry includes patients treated with self-expandable nitinol stents for deep venous obstruction. Routine follow-up visits include serial duplex ultrasound for stent patency assessment. The primary outcome was primary stent patency. The secondary outcome was venous thromboembolisms. We studied the rate of stent occlusion and potentially contributing factors. Results: We included 379 patients: 160 with acute thrombotic, 193 with postthrombotic, and 26 with nonthrombotic deep vein obstruction. The mean age was 46±18 years; 55% were women. The cumulative 3-year primary patency rate was 80.5% (95% CI, 73.0%–88.0%) for acute thrombotic, 59.2% (95% CI, 50.4%–68.0%) for postthrombotic, and 100% for nonthrombotic obstruction (log-rank, P <0.0001). Annualized rates of stent occlusion or venous thromboembolism were 7.8 (acute thrombotic), 15.0 (postthrombotic), and 0 (nonthrombotic) events/100 patient-years. In a multivariable Cox regression model, postthrombotic femoral veins at baseline (hazard ratio, 2.64 [95% CI, 1.53–4.56]) and the number of stents (hazard ratio, 1.22 [95% CI, 1.06–1.40]) were associated with stent occlusion after conditioning for age, sex, and clinically relevant factors. Conclusions: The rate of stent occlusion (patency loss) and venous thromboembolism varies substantially across indications, also with dedicated venous nitinol stents. Patients with postthrombotic femoral veins and those who received multiple stents were characterized by the highest risk. Registration: URL: https://clinicaltrials.gov . Unique identifier: NCT02433054. Abstract : Supplemental Digital Content is available in the text.